(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Firm union of the husband and wife is a vital condition for a glad family life. Islam in this way, demands the subsistence of a marriage and recommends that break of marriage contract ought to be maintained a strategic distance from. At first no marriage is contracted to be disintegrated yet in sad conditions the wedding contract is broken. One of the methods for such dissolution is by method for divorce. Under Muslim law the divorce may occur by the demonstration of the parties themselves or by an announcement of the court of law. Anyway in whatever way the divorce is affected it has not been viewed when in doubt of life. In Islam, divorce is considered as a special case to the status of marriage. Talaaq in its crude sense implies dismission. In its strict significance, it signifies setting free, letting free, or removing any ties or limitation. In Muslim Law it implies opportunity from the subjugation of marriage and not from some other servitude. In legitimate sense it implies dissolution of marriage by husband utilizing suitable words. At the end of the day talaaq is disavowal of marriage by the husband as per the method set somewhere around the law.